THE EFFECT OF CERAMIC WASTE AS COARSE AGGREGATE ON STRENGTH PROPERTIES OF CONCRETE (Nigerian Journal of Technology, 2017)
This paper reports the findings on an experimental investigation of the effect of partial replacement of coarse aggregate with ceramic waste on strength properties of concrete. Compressive strength tests were conducted using 150x150x150mm cube specimens, while tensile strength was investigated using 150x300mm cylinder specimens. Results of tests show that workability, density, compressive and flexural strength of concrete decreased with increase in ceramic waste content. The compressive strength at 90 days curing age for the control sample was 24.67 N/mm2. Compressive strength values at 90 days curing age for  25%, 50% and 75% replacement levels were 21.78 N/mm2, 19.85 N/mm2and 17.85 N/mm2 respectively. The decrease in density and strength was due to ceramic waste being lighter and more porous than normal coarse aggregate. Tensile strength of concrete with ceramic waste decline gradually from 8.39 N/mm2 to 6.13 N/mm2 for the control and 75% replacement samples respectively. This could be attributed to the water absorption capacity and external porcelain nature of the waste material. A production cost savings of 10.7% for 1:2:4 concrete mix was noted at 75% replacement level. This study concludes that ceramic waste could be used for both structural and non-structural works and recommends that beyond 75% replacement level, ceramic waste material should not be used in concrete structures where strength is the major consideration. http://dx.doi.org/10.4314/njt.v36i3.5